2018
DOI: 10.1001/jamaophthalmol.2018.4157
|View full text |Cite
|
Sign up to set email alerts
|

Association of Exfoliation Syndrome With Risk of Indirect Inguinal Hernia

Abstract: IMPORTANCE Exfoliation syndrome (XFS) is a systemic connective tissue disease, and abnormal connective tissue metabolism is implicated in inguinal hernias (IH). Associating XFS with comorbid conditions may illuminate their underlying pathophysiology and affect clinical screening and treatment. Exfoliation syndrome involves altered systemic extracellular matrix (ECM) homeostasis involving elastin metabolism. Hernias occur owing to abnormal ECM synthesis, metabolism, or repair. Inguinal hernias involve weakening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
0
16
0
2
Order By: Relevance
“…Interestingly, STRA6 mutations constitute the only demonstrated cases of human mutations that affect a gene from the retinoid pathway and lead to a complex spectrum of developmental abnormalities including micro/anophthalmia, heart defects, pulmonary dysplasia and diaphragmatic hernia (41,42). A similar disease spectrum, including relative anterior microphthalmos, atrial fibrillation, obstructive pulmonary disease and inguinal hernias, has been reported to occur in PEX patients (9,43,44). Silencing of STRA6 can also cause tissue fibrosis via suppression of STRA6 cascades through upregulation and activation of TGF-ß1 and collagen type I (45).…”
Section: Discussionmentioning
confidence: 59%
“…Interestingly, STRA6 mutations constitute the only demonstrated cases of human mutations that affect a gene from the retinoid pathway and lead to a complex spectrum of developmental abnormalities including micro/anophthalmia, heart defects, pulmonary dysplasia and diaphragmatic hernia (41,42). A similar disease spectrum, including relative anterior microphthalmos, atrial fibrillation, obstructive pulmonary disease and inguinal hernias, has been reported to occur in PEX patients (9,43,44). Silencing of STRA6 can also cause tissue fibrosis via suppression of STRA6 cascades through upregulation and activation of TGF-ß1 and collagen type I (45).…”
Section: Discussionmentioning
confidence: 59%
“…It is associated with other ocular conditions such as cataract, angle closure, retinal vein occlusion, and zonular fragility. It is also associated with multiple systemic vascular conditions, such as renal artery stenosis and aortic aneurysm, as well as cerebrovascular and cardiovascular disease, hearing loss, and elastic tissue disorders, such as pelvic organ prolapse, inguinal hernia, and chronic obstructive pulmonary disease 510…”
mentioning
confidence: 99%
“…Literature review of positive risk factors for XFS in general [Tables 5 - 7 ][ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 ] and XFS in young subjects [ Table 8 ][ 82 83 84 85 86 87 88 89 90 91 …”
Section: Resultsmentioning
confidence: 99%
“…In the Lebanese cohort under investigation, XFS was associated with advanced age, glaucoma, habitual ocular rubbing, and longer time for cataract surgery. While advanced age [ Table 6 ],[ 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 ] glaucoma [ Table 5 ],[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 ] and longer surgery duration[ 100 ] are well established risk factors for XFS [ Table 5 ],[ 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 <...>…”
Section: Discussionmentioning
confidence: 99%